The Presence of International Organizations in the Evolution of the International Law of the Sea : Thirty Years since the Entry into Force of UNCLOS - Oanta, Gabriela A., (International Law E-Books Online, Collection 2025., 2025)
2024 marks thirty years since the entry into force of the United Nations Convention on the Law of the Sea (UNCLOS). The process of adoption of UNCLOS and its influence on the development of the Law of the Sea are a good illustration of the important role that international organizations have played in contemporary international Law of the Sea, as they are the main producers of international norms. This book focuses on the role of the international (universal, regional, and subregional) organizations in the implementation of the provisions of UNCLOS and on how their legal orders have been veritable laboratories in which to test the scope of the provisions or rules of UNCLOS.